SISTEM PEMBUKTIAN DALAM TINDAK PIDANA PENIPUAN MELALUI SARANA E-COMMERCE BERDASARKAN KITAB UNDANG-UNDANG HUKUM ACARA PIDANA DAN UNDANG-UNDANG NOMOR 19 TAHUN 2016 TENTANG PERUBAHAN ATAS UNDANG - UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Syeiqal Afwan Gumilamg; Davit Rahmadan; Adi Tiaraputri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Business fraud through e-commerce means is a fraud that occurs because of the engineering or lies of electronic information by criminals in business through e-commerce means. Victims of fraud through e-commerce means are reluctant to report to law enforcement, while fraud is categorized as ordinary offense. More and more parties are disadvantaged for the actions of the perpetrators of fraud through e-commerce if there is no law that regulates it.This type of legal research is normative law with a normative juridical approach to critically analyze e-commerce-based fraud criminal law norms which aim to explore the disclosure of protection and law enforcement for victims of e-commerce-based fraud. Meanwhile, if viewed from the nature of this research is descriptive. Data collection in this study is a study of documents or library materials.The result of this research is the regulation of the legal system of proof of criminal acts of fraud through e-commerce means in Indonesian criminal law, namely the Criminal Procedure Code only contains the role of proof in Article 183 that judges may not impose a crime on someone unless with at least two valid evidence. In Indonesia, legal regulations regarding e-commerce transactions are still a topic of discussion. Even making legal regulations in e-commerce transactions has created tug of war from two different interests. As a result, this legal regulation has only become a discourse until now. Even if there are rules that regulate e-commerce transaction issues, even that is still very partial and too small. However, this little regulation is not sufficient to accommodate the legal problems that arise in e-commerce transactions. Therefore, the need for comprehensive and integrated arrangements, as well as paying attention to existing arrangements, is something that cannot be denied.Keywords: Evidence System, Fraud, E-Commerce